Sex-specific effects of prenatal exposure to phthalates and bisphenol A on adverse birth outcomes: Results from The Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Jongmin Oh; Surabhi Shah; Kyung A Lee; Eunkyo Park; Dong-Wook Lee; Yun-Chul Hong; Sanghwan Song; Sung Yeon Kim; Huibyeol Park; Hwan-Cheol Kim; Kyoung Sook Jeong; Eunhee Ha (Environment International)
Objectives: Although previous epidemiological studies have reported the effects of fetal exposure to phthalates and phenols on birth outcomes, evidence is still limited. The objective of this study was to investigate whether prenatal exposure to endocrine-disrupting chemicals [EDCs; phthalates and bisphenol A (BPA)] is associated with birth outcomes and whether there are sex-specific effects. Methods: We used data from the Korean CHildren’s ENvironmental health Study (Ko-CHENS) cohort. Exposure to phthalates and BPA was measured by urine tests, and the information on outcomes and confounders was obtained from delivery records, biomarker assessment, and a self-reported questionnaire. We performed multivariate logistic regression to estimate the association between exposure to individual phthalates and bisphenol A and birth outcomes. Additionally, to evaluate the effects of EDC mixture exposure, we performed weighted quantile sum regression analysis. Subgroup analysis stratified by maternal age and sex at birth was performed to examine potential differences in associations. Results: This study included 2,176 mother–child pairs from the Ko-CHENS. We observed a significant association between the risk of PTB and exposure to BPA during early pregnancy and mono-carboxyoctyl phthalate (MCOP) during late pregnancy, with odds ratios of 1.23 (95% CI: 1.01, 1.49) and 1.29 (95% CI: 1.03, 1.62), respectively. Additionally, there was a significant association between exposure to MCOP during early pregnancy and the risk of LBW (OR: 1.39, 95% CI: 1.03, 1.89). For male infants in particular, exposure to MCOP during early pregnancy was associated with the risk of LBW (OR: 2.44, 95% CI: 1.43, 4.15), and exposure to MCOP during late pregnancy was associated with the risk of PTB (OR 1.45, 95% CI: 1.05, 2.02). Conclusions: This study suggests a potential association between exposure to BPA during early pregnancy and PTB, while exposure to MCOP during late pregnancy was associated with increased PTB risk in male infants.